The Problem of Violence Against Women: Sociological Analysis (Zien Journal of Social Sciences and Humanities, 2023)
Public health is increasingly becoming an integrated indicator of a high level of Social Development. In this regard, it is of socio-economic importance to strengthen the health of the population, increase the effectiveness of the activities of health institutions in the prevention and Prevention of diseases. The international community recognizes that young people who are healthy and fit, enterprising, with modern knowledge and skills occupy an extremely important place in the development of any country. This article analyzes the peculiarities of the health system of the countries of France, Great Britain, Japan, which are among the developed countries of the world.